Effect of dietary beta-agonist supplementation on live performance, carcass characteristics, carcass fabrication yields, and strip loin tenderness and sensory traits - Arp, Travis Steven, author; Belk, Keith, advisor; Woerner, Dale, committee member; Tatum, J. Daryl, committee member; Pendell, Dustin, committee member (Colorado State University. Libraries, 2012)
Beef steers (n = 3,906) were fed at a commercial feed yard to evaluate the effects of beta-adrenergic agonist supplementation on live performance, carcass characteristics, carcass fabrication yield and strip loin tenderness and palatability. Steers were weighed and ultrasonic carcass measurements were collected for allocation into four feeding blocks. Within each block, approximately 100 steers were assigned two a pen that was assigned one of five treatments, including: No beta-agonist; Ractopamine hydrochloride (RH) fed at 200 mg/hd/d for the final 30 d of finishing (RAC200); RH fed at 300 mg/hd/d for the final 30 d of finishing (RAC300); RH fed as a 400 mg/hd/d top dress for the final 30 d of finishing (RAC400); and Zilpaterol hydrochloride (ZH) fed at 6.8 g/ton beginning 23 d before slaughter, with a withdrawal period starting 3 d before to slaughter (ZIL). The study design included eight replicates (pens) per treatment (two per block). Each feeding block was harvested on consecutive weeks. Each week, carcass parameters were measured and strip loin samples were collected from 18 carcasses per pen (720 total samples) for Warner-Bratzler and Slice Shear Force, and trained sensory analysis. Subsamples of eight carcasses per pen (320 total samples) were selected for whole carcass fabrication yield. Final BW was not affected by treatment (P = 0.2892), but there was a tendency for cattle receiving βAA supplementation to be heavier compared to controls (P = 0.0681). Average daily gain and F:G ratio was improved with treatment of βAA (P < 0.05). Carcasses from the ZIL and RAC400 treatments had the heaviest HCW, and were significantly heavier than CON and RAC200 treatments (P < 0.05). The ZIL treatment also recorded the highest dressing percent and carcasses had the largest LMA compared to all other treatments (P < 0.05). USDA yield grade and marbling score were reduced due to βAA supplementation (P < 0.05). Differences in marbling score reduced the frequency of carcass qualifying for the CAB premium in βAA treated cattle (P < 0.05), while also accounting for a decrease in the frequency of carcasses grading choice and an increase in the percentage of carcasses grading select for cattle receiving βAA supplementation compared to controls (P < 0.05). The percentage of YG1 carcasses was increased and the frequency of YG3 carcasses was decreased due to βAA treatment (P < 0.05). Treatment with dietary βAA elicited the greatest response in subprimal yield in cuts from the round. Zilpaterol treatment carcasses reported the highest total saleable yield, and were greater than all RAC treatments (P < 0.05). Warner-Bratzler and SSF was affected by treatment (P < 0.05), with an increase in shear force values with increased dose and potency of βAA's. Likewise, the percentage of steaks shearing greater than 4.4 and 20 kg for WBSF and SSF, respectively, was increased with βAA supplementation (P < 0.05). Tenderness attributes were ranked lower for steaks from βAA treatments by trained sensory panelists (P < 0.05). There were no differences detected by panelists for juiciness or beef flavor attributes.
Keywords: steers; growth; tenderness; beta-agonist; carcass